A Retrospective Case Series Study on Drug Adherence Patterns and Associated Complications in PLHIV on HAART in a Tertiary Care Teaching Hospital - Khan, Zahed Ulla; Mathai, Jibin; Mudkappa Keshannavar,Shalavadi, Mallappa (Journal of Pharmacy Practice and Community Medicine)
Background: HIV/AIDS is reduced from a formerly lethal disease to a manageable chronic condition post advent of ART, the art era has promised new life standards and improving QOL of PLHIV, anyhow there are issues regarding adherence patterns where both patterns of adherence come with certain complications. Objectives: To retrospectively analyze for ADRs that are due to Antiretrovirals. To study the most prevalent reasons behind admission to hospital in PLHIV. To study mean age and inter-age prevalence of OIs and Drug-induced manifestations in PLHIV. To provide a database aiding in framing policies for the betterment of PLHIV. To synthesize results that can improve the QOL of PLHIV. Materials and Methods: We searched for all case files from 2018 to 2020 to screen for reasons why PLHIVs were admitted to a tertiary care teaching hospital and then looked into Google Scholar, Pubmed, etc. with keywords such as HIV, PLHIV, Complications of HAART, and many such to study the underlying reasons for the outcome seeking intervention. We also analyzed prescription patterns in the meanwhile to arrive at conclusions about various complications and modalities of treatment for the same. Results and Conclusion: Anemia is seen to be very prevalent amongst PLHIV accounting for about 54% of the population, Hepatotoxicity, Lipodystrophy, and an array of metabolic disorders can be linked to Drugs, and outcomes which were rare and difficult to manage were usually due to the nonadherent pattern. Although new incidences of Cranial lesions are being reported research in this direction is quasistatic post 90’s. The most common drugs that cause ADRs belong to the class of NNRTIs followed by protease inhibitors. Although new novel drugs are available, their prescription is almost not seen. And more awareness is needed in this regard.
Keywords: HIV; AIDS; HAART; Adverse drug reaction; PLHIV; QOL